The Expression, Morphology, and Clinical Characteristics of Fibroblast Growth Factor-10 in Breast Cancer - Molashahi, Samira; Farhud, Dariush D; Saffari, Mojtaba; Ebrahimi, Elmira; Emamirazavi, Amirnader; Shirkoohi, Reza (Asian Pacific Journal of Cancer Biology, 2021)
Background: Fibroblast growth factor-10 (FGF-10) is a member of a superfamily with characteristics of epithelial cell proliferation and embryonic development and is assumed to have a role in a phenomenon called the epithelial-mesenchymal transition (EMT). The previous study has revealed the critical role of FGF-10 in type III EMT in breast cancer cell lines. The mentioned finding, demonstrates the possible role of this factor in type III EMT in cancers with different origins such as breast. The present study investigated the expression of FGF-10 as a mitotic-inducing growth factor, normally has a low expression in breast tissues amongst breast cancer patients. Materials and Methods: 67 breast cancer tissues and 8 normal breast tissues were randomly selected from the Iran national tumor bank. The FGF-10 gene expression analysis was performed after the RNA expression using the real-time RTPCR, which was followed by the Student’s t-test statistical analysis. Results: The findings revealed that the relative expression of FGF-10 was elevated in tumor tissues as compared with normal breast tissues, and the higher expression had a direct correlation with the progression of clinical and pathologic staging. The expression was also significantly higher in triple-negative breast cancer and p53 null tissues. Conclusion: Taken together, it is suggested that, although in some variables it was not significant but generally the invasion and migration in tumor tissues are the same as in-vitro analysis as indicated before, and the expression has a direct relationship with the molecular presentation and clinical -pathological progression.